The Effect of Snakehead Fish on Superoxide Dismutase Levels and Gastric Histopathological Features in a Rat Model of Liver Cirrhosis - OK Yulizal; Fitorius Gaurifa; Yuliani Mardiati Lubis (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2025)
Liver cirrhosis is a chronic disease that frequently leads to complications such as portal hypertensive gastropathy (PHG), which is characterized by increased oxidative stress and reduced activity of antioxidant enzymes such as Superoxide Dismutase (SOD). Snakehead fish (Channa striata) is known to contain high levels of albumin and amino acids that function as antioxidants and anti-inflammatory agents. This study aimed to analyze the effect of Channa striata extract on SOD levels and gastric histopathological features in a rat model of liver cirrhosis. This experimental research employed a randomized post-test-only control group design involving 30 male Wistar rats divided into five groups: normal control (K1), cirrhosis without treatment (K2), and three cirrhosis treatment groups receiving Channa striata extract at doses of 100 mg/kgBW (K3), 150 mg/kgBW (K4), and 200 mg/kgBW (K5). SOD levels were measured through tissue homogenization, while gastric histopathology was examined using Hematoxylin–Eosin staining. The results showed a significant increase in SOD levels with a dose–response pattern (p < 0.001) and a gradual improvement in gastric histopathology (p > 0.05). In conclusion, Channa striata extract has the potential to enhance antioxidant activity and improve gastric histological structure in rats with liver cirrhosis.